2017
DOI: 10.1017/s0030605316001095
|View full text |Cite
|
Sign up to set email alerts
|

Livestock depredation by large predators and its implications for conservation and livelihoods in the Karakoram Mountains of Pakistan

Abstract: Livestock depredation has particular significance in pastoral societies across the Himalayas. The dynamics of depredation by the snow leopard Panthera uncia and wolf Canis lupus were investigated by means of household surveys in the Hushey Valley, in the Karakoram Mountains of Pakistan. During 2008–2012 90% of the households in the valley lost livestock to snow leopards and wolves, accounting for 0.8 animals per household per year. The cost of depredation per household was equivalent to PKR 9,853 (USD 101), or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
(33 reference statements)
1
15
0
Order By: Relevance
“…The economic loss due to depredation in Hindu Kush, Karakoram and Himalaya region is quite significant like in upper Mustang region of Nepal, it accounts for US$ 44,213 per year 7 . Similarly, US$ 12,252 per year is lost in Jigme Singye Wangchuck National Park 18 of Bhutan and loss of US$ 12,905 per year has been recorded for Hushey valley in Central Karakorum National Park, Pakistan 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The economic loss due to depredation in Hindu Kush, Karakoram and Himalaya region is quite significant like in upper Mustang region of Nepal, it accounts for US$ 44,213 per year 7 . Similarly, US$ 12,252 per year is lost in Jigme Singye Wangchuck National Park 18 of Bhutan and loss of US$ 12,905 per year has been recorded for Hushey valley in Central Karakorum National Park, Pakistan 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Predation fosters intolerance among such impoverished pastoralists and often leads to persecution [ 5 , 9 , 10 ]. The conflict between humans and snow leopards is reported across snow leopard range countries, causing significant economic losses to local pastoralists, thereby creating a strong dislike towards the species and decreased support for its conservation [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is signi cant to highlight that the data collection involved a survey-based quantitative method to reach the main causes, perceptions, and damages caused by the carnivores. Similar methods were followed in previous studies 22,24 . In this questionnaire survey, we collected the data using the quantitative method on the parameter such as livestock owned, type of livestock and mortality by predators and diseases, predators number and status, threats to wild carnivores, perceptions, and attitudes of people towards carnivore conservations, humancarnivore con ict experience and the nancial loss of animals by predators and diseases.…”
Section: Data Collectionmentioning
confidence: 91%
“…Herders claimed that they could distinguish between a carcass killed by a wolf attack on animal's hindquarters and snow leopard attack on the neck or throat as well as by the presence of predators' tracks on the kill site 19 . Previous studies indicated an economic lost of livestock to predators were valued in the dollar and local prices, an estimated US$ 44,213 in the upper Mustang region 7 , US$ 12,252 in Jigme Singye Wangchuck National Park 20 , US$445,539 (US$99,009 ) per year in the Pamir regions 21 and PKR 4,926,596 (USD 51,620) in Hushey valley 22 .These mammalian predators preyed on many livestock in Misgar valley. However, the depredation and its impact not yet been studied in this valley.…”
Section: Introductionmentioning
confidence: 99%